Association Between Coffee Consumption Patterns and Hemoglobin Levels in Female Medical Students of UMSU Medical Faculty - Rema Pasaribu; Eka Febriyanti (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Anemia remains a pervasive global public health issue, particularly among women of reproductive age. In Indonesia, the prevalence of anemia in young women is exacerbated by dietary habits that inhibit iron absorption. This study aims to determine the association between coffee consumption patterns and hemoglobin levels among female medical students at the Faculty of Medicine, Muhammadiyah University of North Sumatra (UMSU). Method: An analytical observational study utilizing a cross-sectional design was conducted with 84 female students selected via consecutive sampling. Coffee consumption patterns were assessed using a Food Frequency Questionnaire (FFQ), categorized into infrequent (3x/week) and frequent (≥3x/week) intake. Hemoglobin levels were measured quantitatively. Data were analyzed using the Mann-Whitney U test to compare median hemoglobin levels between the two groups. Results: The cohort was dominated by 20-year-old students (34.5%). A significant majority exhibited frequent coffee consumption patterns (86.9%, n=72) compared to infrequent consumers (13.1%, n=12). The median hemoglobin level across the sample was 11.35 g/dL. Statistical analysis revealed a significant difference in hemoglobin levels between the frequent and infrequent coffee consumption groups (p 0.01). Conclusion: There is a statistically significant association between high-frequency coffee consumption and lower hemoglobin levels among female medical students. These findings highlight the need for nutritional education regarding the timing of caffeine intake to mitigate the risk of anemia